TINJAUAN YURIDIS OPTIMALISASI FUNGSI PENGAWASAN DPRD TERHADAP KEBIJAKAN GUBERNUR DKI JAKARTA - Torang, Lawrence Averino Magistrate; Poltak Siringoringo; Haposan Sahala Raja Sinaga (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
This study analyzes the optimization of the implementation of the Rights of the DKI Jakarta of House Representative Council (DPRD) in terms of carrying out the supervisory function of every policy of DKI Jakarta's Governor. This research is normative juridical research, namely by approaching the legislation, secondary legal materials in the form of interviews with members of the DKI Jakarta of House Representative Council, books, and journals. And qualitatively processed. As for the results of the research on the formulation of the first problem, in the implementation of the rights of the DKI Jakarta of house representative council to carry out the supervisory function of the DKI Jakarta governor, it was found that there was a difference in political views between the factions, thus hampering a regulation or provision in the implementation of the supervisory function of the DKI Jakarta of house representative council. The regulatory barrier in question is the requirement for a quorum formulation to propose and make a decision. The result of the second study is that there is no striet sanction if the regional oh house representative council does not carry out its functions properly. In general, if every faction in the DKI Jakarta of House Representative Council has the same think on a policy issued by the governor, then the supervisory function should be able to run optimally. And if the regional people's representative councils do not carry out their supervisory functions properly, there should be strict sanctions in the legislation.